2023
DOI: 10.1039/d3cc03121g
|View full text |Cite
|
Sign up to set email alerts
|

3D cauliflower-like Ni foam: a high-efficiency electrocatalyst for ammonia production via nitrite reduction

et al.

Abstract: Electrochemical nitrite (NO2−) reduction offers a promising and environmentally friendly pathway for ammonia (NH3) production and the elimination of NO2− pollution. The conversion process however involves a complex six-electron transfer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The XPS study revealed the valence states 50 of the elements present in pristine Bi 3 O 4 Br and Mn–Bi 3 O 4 Br (Fig. S6†).…”
Section: Resultsmentioning
confidence: 99%
“…The XPS study revealed the valence states 50 of the elements present in pristine Bi 3 O 4 Br and Mn–Bi 3 O 4 Br (Fig. S6†).…”
Section: Resultsmentioning
confidence: 99%
“…15–18 The electrochemical conversion of waste NO 3 − into valuable products in the form of N 2 /NH 3 under mild reaction conditions offers a potential solution to the problem of nitrate and/or nitrite pollution. 16,19–24 Additionally, this process presents an environmentally friendly and sustainable alternative to the conventional Haber-Bosch method for ammonia synthesis; 25–27 hence, it is a hot topic in the field of electrocatalysis. The eight electron transfer process associated electrochemical NO 3 − reduction reaction (NO 3 RR) to NH 3 is regarded as a promising means of converting NO 3 − without causing secondary contamination.…”
Section: Introductionmentioning
confidence: 99%
“…NO x is a N-containing pollutant found ubiquitously in groundwater and surface water aquifers, causing public health and serious environmental problems around the world. Nitrate (NO 3 – ) is a type of NO x with a low cleavage energy of 204 kJ/mol for the NO bond and high water solubility. , NO 3 – is considered an attractive N-source for electrosynthesis of NH 3 from the point of view of promoting environmental protection and facilitating NH 3 synthesis. , Furthermore, due to the chemical properties of NO 3 – , the electrocatalytic nitrate reduction reaction (NO 3 RR) to NH 3 possesses much faster kinetics compared with N 2 RR. Since the electroreduction of NO 3 – to NH 3 involves a multiple proton–electron-transfer process, efficient electrocatalysts need to be urgently developed.…”
Section: Introductionmentioning
confidence: 99%